The participation of public officials and their relationship with organized crime in a district of the province of Chiclayo - Tenorio, Yenny Acuña; Gonzales, Génesis Cabrales; Estela, Greysi Carpio; Carrasco, Anai Huancas; Seminario, Luz Ramírez; Cruz, Darwin Zurita; Seclén, Gustavo Adolfo Ventura (Edelweiss Applied Science and Technology, 2025)
The present scientific research study was associated with SDG 16: peace, justice, and strong institutions. Our general objective was to determine the relationship between the participation of public officials and organized crime in a district of the province of Chiclayo. To obtain the data, a basic research methodology with a quantitative approach was developed, which fits a non-experimental correlational design. The population consisted of 165,456 residents aged between 25 and 45 years in the district of José Leonardo Ortiz, and a total sample of 384 participants was obtained through probabilistic sampling. Given this, non-experimental correlational statistics were applied, and using the Spearman statistical method, data were obtained to respond to the proposed objectives. The main result revealed a correlation between the variable public officials and organized crime, which was verified through the Spearman statistical process, yielding a result of r=0.660, considered moderate. Additionally, a medium level of participation of public officials (55.7%) and a high level of organized crime (64.3%) were found, related to the dimensions of corruption (r=0.427), abuse of power (r=0.610), and institutional response (r=0.579). It is concluded that public officials are elements that facilitate the establishment and expansion of organized crime because the latter enjoys the protection provided by these officials.